EVALUASI ADVERSE DRUG REACTION ANTIDIABETES BERDASARKAN ALGORITMA NARANJO DI BANGSAL RAWAT INAP RS PKU MUHAMMADIYAH YOGYAKARTA PERIODE DESEMBER 2011-JANUARI 2012 - Fitriyani, Fitriyani; Supadmi, Woro (Pharmaciana, 2012)
This study is aimed to evaluated the antidiabetic adverse reaction using theNaranjo algorithm for diabetes mellitus patients in PKU Muhammadiyah HospitalYogyakarta for period December 2011-January 2012. This study used descriptivemethod. The data was collected from the medical record and interviews from patientswith diabetes mellitus who had used antidiabetic drugs after 3 days. The data wereanalyzed using the Naranjo algorithm. The results showed that during the periodDecember 2011-January 2012 there were 17 male patients and 14 female patients withdiabetes mellitus. The antidiabetic drugs that used to patients were metformin,metformin combined with glibenclamide, metformin combined with insulin, thecombination with insulin and insulin glimepirid. Then, the study showed that Naranjoalgorithm method was not suitable for evaluation the antidiabetic adverse reaction fordiabetes mellitus patients in PKU Muhammadiyah Hospital in Yogyakarta for periodDecember 2011-January 2012, because from 10 questions on the Naranjo algorithmthere were only 4 questions that could be answered. Its because there was not data toanswer questions. Research on the side effects cohort method should be done with theinterview and patient monitoring.